Analisis Pengelolaan Administrasi Desa dalam Meningkatkan Kualitas Pelayanan Masyarakat - Zaki Al Mubarok; Moh As'adi (CV. Lentera Literasi Indonesia, 2026)
Village administrative management is one of the important factors in supporting the implementation of effective and high-quality public services. A well-organized village administration system can assist village officials in managing the data, documents, and information required to provide services to the community in a timely, accurate, and accountable manner. This study aims to analyze village administrative management in supporting community services and to examine its contribution to improving the quality of public services. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving village officials and community members as service recipients. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which includes data collection, data condensation, data display, and conclusion drawing. The validity of the data was ensured through source triangulation and technique triangulation. The results of the study indicate that effective village administrative management plays a significant role in supporting the implementation of community services. A well-organized and systematic administrative system enables village officials to manage data efficiently, accelerate service processes, improve information accuracy, and support the effectiveness of village governance activities. Furthermore, village administrative management contributes significantly to improving the quality of public services through enhanced service efficiency, transparency, accountability, service reliability, and increased public trust in the village government. Therefore, strengthening the village administrative system, improving the competence of village officials, and utilizing information technology are essential factors in achieving high-quality public services that are oriented toward community satisfaction.